The South China Sea arbitration toward an international legal order in the oceans - Tanaka, Yoshifumi (Oxford New York Hart Publishing, 2019)
"Beyond the scope of the settlement of the dispute between the Philippines and China, the South China Sea arbitral award can be thought to significantly influence the development of international law and the law of the sea. Thus this book seeks to examine the South China Sea arbitration from the perspective of the development of public international law and its limitations. Specifically this book addresses the issues of jurisdiction of the Annex VII Arbitral Tribunal, historic rights, legal status of maritime features, lawfulness of various activities of China, and the role of the South China Sea arbitration in the settlement of the dispute between the Philippines and China. In considering these issues, this book examines the South China Sea arbitration in three respects: (i) the clarification of relevant rules and obligations under the LOSC as well as international law, (ii) the protection of community interests at sea, and (iii) considerations of time elements in international law. In so doing, this book attempts to consider the establishment of an international legal order in the oceans"--
Jurisdiction and Admissibility -- The 'Nine-dash Line' and China's Claim to Historic Rights in the South China Sea -- The Legal Status of Maritime Features in the South China Sea -- Lawfulness of Chinese Activities in the South China Sea -- Legal Implications of the South China Sea Arbitration Awards -- General Conclusion
Includes bibliographical references and index.
Keywords: Jurisdiction (International law); Maritime boundaries; China -- Trials, litigation, etc; Philippines -- Trials, litigation, etc; South China Sea -- International status